Correlation between body mass index and agility in hockey extracurricular participants - Ahmad Ulul Bisri Husni; Shinta Masitho Windriyani; Anangga Widya Pradipta (Sriwijaya Journal of Sport, 2024)
The research aims to investigate the relationship between BMI and agility in extracurricular hockey participants at SMAN 1 Bululawang. The research method employs correlation analysis from weight and height measurements for BMI, while agility is assessed using a 10-meter shuttle run test. Data analysis utilizes SPSS 26 and correlation analysis. Results from the BMI of male participants categorized 3 as severely underweight, two as slightly underweight, and four as normal weight. Female participants' BMI categorized one as severely underweight, three as slightly underweight, seven as normal weight, and one as overweight. Regarding agility, results showed four male participants lacked agility, and five severely lacked agility. Female participants had 12 categorized as severely lacking agility. Data analysis revealed a correlation coefficient of rxy= 0.484<rtable= 0.666 and a significance value of 0.187>0.05 for male participants. For female participants, the correlation coefficient was rxy= 0.426<rtable= 0.576 and the significance value was 0.168>0.05. Therefore, the data analysis indicates no significant relationship between BMI and agility among extracurricular hockey participants at SMAN 1 Bululawang.